2004
DOI: 10.1023/b:lahu.0000046430.65485.1f
|View full text |Cite
|
Sign up to set email alerts
|

Priming unconscious racial stereotypes about adolescent offenders.

Abstract: Two studies examined unconscious racial stereotypes of decision makers in the juvenile justice system. Police officers (Experiment 1) and juvenile probation officers (Experiment 2) were subliminally exposed to words related to the category Black or to words neutral with respect to race. In a presumably unrelated task, officers read 2 vignettes about a hypothetical adolescent who allegedly committed either a property crime (shoplifting from a convenience store) or an interpersonal crime (assaulting a peer). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(154 citation statements)
references
References 48 publications
2
139
1
Order By: Relevance
“…The evidence is not strongly supportive of the idea that court official perceptions of youth from different racial groups mediate the influence of race on sentencing outcomes (in this case, recommendations), and others have critiqued the conclusions drawn from this study (e.g. Graham & Lowry, 2004), but it nonetheless serves as a good example of the type of research that can help to advance our understanding of how the perceptions of racial minorities held by legal decision-makers may influence sentencing outcomes. There are, of course, other good examples in the literature of studies that inspect more closely the thoughts and feelings of courtroom decision-makers (e.g.…”
Section: Determining How/why Race Influences Sentencingcontrasting
confidence: 66%
See 1 more Smart Citation
“…The evidence is not strongly supportive of the idea that court official perceptions of youth from different racial groups mediate the influence of race on sentencing outcomes (in this case, recommendations), and others have critiqued the conclusions drawn from this study (e.g. Graham & Lowry, 2004), but it nonetheless serves as a good example of the type of research that can help to advance our understanding of how the perceptions of racial minorities held by legal decision-makers may influence sentencing outcomes. There are, of course, other good examples in the literature of studies that inspect more closely the thoughts and feelings of courtroom decision-makers (e.g.…”
Section: Determining How/why Race Influences Sentencingcontrasting
confidence: 66%
“…One recent example of the kind of experimental study that represents a good supplement to existing efforts to detect racial discrimination is Rachlinski, Johnson, Wistrich, and Guthrie's (2009) study of unconscious racial bias among trial judges, in which judges were recruited from a variety of contexts and given Implicit Association Tests (IAT) and then evaluated in terms of how unconscious biases affect sanction choices in hypothetical cases. This study and others like it in the area of mock jury decision-making illustrate nicely the kind of research that could enhance current scholarship on race and sentencing (Eberhardt, Davies, Purdie-Vaughns, & Johnson, 2006;Graham & Lowry, 2004;Levinson, 2007;Levinson & Young, 2010). Such studies serve as an example that this type of research is feasible, and they stimulate interest in applying similar approaches to other samples (e.g.…”
Section: Enhancing Efforts For Detecting Racial Discrimination and Otmentioning
confidence: 58%
“…These attributions about youth then shaped officials' assessments of the threat of future crime and sentence recommendations. Graham and Lowry (2004) critique Bridges and Steen and suggest that attributions about adolescent offenders by court officials involve a more complex set of characterizations involving more than just the assessment of external and internal factors. In addition to whether a cause of delinquency is considered internal or external to a person, Graham and Lowry (2004) examine how controllability and stability influence processing.…”
Section: Focal Concerns and Causal Attributionsmentioning
confidence: 99%
“…On the other hand, some forms of ritualized teasing that have prosocial (group bonding) functions within African American culture, like "playin the dozens" and "signifyin," might be interpreted incorrectly by others as verbal harassment (e.g., Boxer, 1997). And racial stereotypes that associate being Black with violence and hostility are pervasive enough in this culture that perceivers may unknowingly attribute ambiguous behavior by African American youth to aggressive rather than benign intent (e.g., Devine, 1989;Graham & Lowery, 2004). In other analyses with this sample, we found that teachers also perceived African American boys as more aggressive than their peers from other ethnic groups and that these boys were more likely to be suspended from school (Markoe, 2003).…”
Section: Ethnicity Victimization and Aggressionmentioning
confidence: 99%